Grotesque ambivalence : melancholy and mourning in the prose work of Albert Drach - Cosgrove, Mary (Conditio Judaica ;, 2004)
The first English language study of Albert Drach's (1902-1995) prose work explores the originality of Drach's autobiography in the context of current Holocaust debates. Special attention is paid throughout to the relationship between Drach's comic-grotesque language and the melancholy mode of representation in the Holocaust trilogy. Both passionate and critical, Drach's prose lays bare the totalitarian power mechanisms of his time.